Educational Quality Management in Elementary Schools: Measuring the Validity and Reliability of Maharah Qira’ah Test Items - Ahmad Mashadar Hilmi; Muhammad Syihabul Ihsan Al Haqiqy; Aminudin; Rahmah Fadhilah Agustina (Journal of Educational Management Research, 2025)
This study aims to evaluate the quality of test items by analyzing their validity, reliability, difficulty level, discriminating power, and distractor effectiveness in measuring students’ learning outcomes. A descriptive quantitative design was employed, involving sixth-grade students of Tarbiyatus Shibyan Elementary School, Duduksampeyan Gresik, during the 2024/2025 academic year. Data were collected through documentation of students’ test results and analyzed using SPSS version 25 and Microsoft Excel. The findings reveal that most items meet the criteria for validity, as indicated by r-values exceeding the r-table or significance levels below 0.05. The reliability coefficient (Cronbach’s Alpha) also exceeds 0.6, demonstrating strong internal consistency. The difficulty level analysis shows that 68% of the items fall into the moderate category, with no items classified as difficult. However, the discriminating power is predominantly poor, with 72% of items showing indices below 0.19, and 24 items contain ineffective distractors. These results imply the need for improved item construction to ensure more accurate, fair, and balanced assessments in elementary education